PERAN KEPRIBADIAN DAN GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA KARYAWAN (Studi pada KSP. MITRA SUKSES SINGASARI) - Moeljokismono, Bambang (Fakultas Ekonomi Universitas Wisnuwardhana, 2016)
This study used a qualitative descriptive research design. The datacollection was done by using interviews and observation. As a leader musthave a strong personality , solid, according to the demands of theorganization as well as a model for individuals under his leadership.Furthermore, a leader must have a humanizing character that will makepeople who lead happy , and feel comfortable doing the job retention or dayto-day tasks. But be aware that personality alone is not enough to bestrengthened with leadership style .Keywords : Personality , Leadership Style, Performance